1997
DOI: 10.1083/jcb.139.4.963
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Stabilization in Pressure Overload Cardiac Hypertrophy

Abstract: Increased microtubule density, for which microtubule stabilization is one potential mechanism, causes contractile dysfunction in cardiac hypertrophy. After microtubule assembly, α-tubulin undergoes two, likely sequential, time-dependent posttranslational changes: reversible carboxy-terminal detyrosination (Tyr-tubulin ↔ Glu-tubulin) and then irreversible deglutamination (Glu-tubulin → Δ2-tubulin), such that Glu- and Δ2-tubulin are markers for long-lived, stable microtubules. Therefore, we generated antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 55 publications
7
122
0
Order By: Relevance
“…Therefore, microtubules appear to function as negative regulators of muscle contraction (Webster, 2000). In agreement with this idea, cardiac hypertrophy and failure correlate with increases in Glu-tubulin and MAP4 levels (Sato et al, 1997;Belmadani et al, 2002;Takahashi et al, 2003). It is an exciting possibility, then, that mis-regulation of MURF-2 (and MURF-3) levels also could contribute to human contractile dysfunction.…”
Section: Murf-2 and Intermediate Filamentssupporting
confidence: 52%
“…Therefore, microtubules appear to function as negative regulators of muscle contraction (Webster, 2000). In agreement with this idea, cardiac hypertrophy and failure correlate with increases in Glu-tubulin and MAP4 levels (Sato et al, 1997;Belmadani et al, 2002;Takahashi et al, 2003). It is an exciting possibility, then, that mis-regulation of MURF-2 (and MURF-3) levels also could contribute to human contractile dysfunction.…”
Section: Murf-2 and Intermediate Filamentssupporting
confidence: 52%
“…Several studies have previously shown that Nav1.5 channels are delivered to their final destination on the membrane through the microtubule network 19, 35. Although microtubule network density was increased in TAC cardiomyocytes, the observed increased detyrosinated tubulin (ie, Glu‐tubulin) levels indicate that the microtubule network is less dynamic25 and, thus, potentially less efficient 36, 37, 38. It is, therefore, reasonable to speculate that the increased Glu‐tubulin observed in our experiments is associated with impaired Nav1.5 delivery at any subcellular location.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, active transport is required for this purpose, and microtubules supply this function: the dynein family of motor proteins moves these cargoes along microtubules toward the cell center, and the kinesin family of motor proteins moves these cargoes along microtubules from the nuclei toward the cell periphery. In cardiac hypertrophy, the microtubules not only proliferate but also become heavily decorated by microtubule-associated protein-4, the predominant cardiac microtubule-associated protein (23,28). One consequence of this is that the normal microtubule transport function is sterically inhibited by the presence of microtubule-associated protein-4 on these transport tracks, and as one example that may help explain ␤-adrenergic receptor downregulation in cardiac hypertrophy and failure, we have shown that activated G proteincoupled receptors fail to be recycled properly to the cell membrane (2,3).…”
Section: Future Directionsmentioning
confidence: 99%
“…The most definitive solution, however, would be to close the loop and address the microtubule hypothesis directly in a context apart from hemodynamic alterations in vivo or microtubule alterations in vitro. On the basis of some of our other work defining the basic causes of microtubule network densification in cardiac hypertrophy (21,23,28), I very recently tested, via a collaboration with F. Cabral and D. R. Menick, the effects of ␤ 1 -tubulin mutants that had been selected for their effects on microtubule stability and then expressed in the hearts of transgenic mice (4). We found that when intrinsic microtubule stability was increased as an isolated variable, the contractile defects characteristic of pressure-overloaded hypertrophied myocardium were reproduced.…”
Section: Is There a Specific Link Between Microtubule Network Densitymentioning
confidence: 99%